Supplementation of caffeine and sodium bicarbonate together could not improve performance and performance-related factors in CrossFit participants: a randomized, double-blind, placebo-controlled study - Amirhosein Ziyaiyan; Fatemeh Shabkhiz; Martin Hofmeister (Taylor & Francis Group, 2023)
Background CrossFit includes weightlifting, powerlifting, and gymnastics in various combinations of overloads and repetitions with limited rest periods or no rest between training sets. Due to the novelty of CrossFit, there are few studies on the effect of nutritional strategies on the acute response to this type of sports activity. This study examined the effect of caffeine (CAF) and sodium bicarbonate (NaHCO3) ingestion separately and in combination on the performance and rate of perceived exertion (RPE) during the Cindy CrossFit workout (Cindy) in CrossFit participants. Method In a double-blind, crossover, randomized, placebo-controlled trial, 20 CrossFit participants underwent five experimental conditions, including control (CON), placebo (PLA), CAF, NaHCO3, and CAF + NaHCO3 (7 days to wash-out between assessment sessions) before completing the Cindy protocol (age: 22.30 ± 2.88 years, body mass index: 25.22 ± 2.51 kg/m2). Capsules containing 6 mg/kg body weight (BW) CAF were consumed 50 min before the Cindy workout while 0.3 g/kg BW NaHCO3 was consumed for 3 days, leading to 120, 90, and 60 min before the Cindy workout. Performance, RPE, muscular power (MP), handgrip strength (HGS), and maximum heart rate (MHR) were measured before and shortly after the Cindy. Results The performance of CrossFit participants during the Cindy protocol was not significantly improved following CAF, NaHCO3, and CAF + NaHCO3 (P > 0.05). In contrast, RPE during and at the end of the Cindy was significantly decreased following CAF + NaHCO3 consumption compared to PLA and CON (P = 0.001, P = 0.02). However, MP (P = 0.82) and HGS (P = 0.52) were not significantly different between conditions. Also, MHR was significantly greater following CAF, NaHCO3, and CAF + NaHCO3 consumption than CON (P = 0.01). Conclusion CAF + NaHCO3 supplementation decreased RPE despite significantly increased MHR, but with no significant effect on performance, HGS, or MP. Therefore, CrossFit participants may benefit from the ergogenic effects of CAF and NaHCO3 when consumed separately or together.